2021
DOI: 10.1111/gcb.15892
|View full text |Cite|
|
Sign up to set email alerts
|

ForestTemp – Sub‐canopy microclimate temperatures of European forests

Abstract: Ecological research heavily relies on coarse-gridded climate data based on standardized temperature measurements recorded at 2 m height in open landscapes. However, many organisms experience environmental conditions that differ substantially from those captured by these macroclimatic (i.e. free air) temperature grids. In forests, the tree canopy functions as a thermal insulator and buffers sub-canopy microclimatic conditions, thereby affecting biological and ecological processes. To improve the assessment of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
75
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(80 citation statements)
references
References 64 publications
3
75
0
2
Order By: Relevance
“…The cooling effects associated with forest canopy cover is also widely reported in the terrestrial and freshwater realms Nakamura 1999, Haesen et al 2021). Extensive monitoring networks in European forests revealed that subcanopy air temperatures were cooler than the free air temperatures by 2.0 ℃ on average (Haesen et al 2021). The Earth's subsurface factors, namely the geology, also contribute to local thermal heterogeneity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cooling effects associated with forest canopy cover is also widely reported in the terrestrial and freshwater realms Nakamura 1999, Haesen et al 2021). Extensive monitoring networks in European forests revealed that subcanopy air temperatures were cooler than the free air temperatures by 2.0 ℃ on average (Haesen et al 2021). The Earth's subsurface factors, namely the geology, also contribute to local thermal heterogeneity.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of Antarctic active layers, Hrbáček et al (2017) reported a distinct ground thermal regime between lithologically different sites due to thermal conductivity controlled by the geology. More importantly, effect of these covariates on local thermal conditions are not always uniform and can vary along environmental gradients (Hilderbrand et al 2014, Jucker et al 2018, Ehbrecht et al 2019, De Frenne et al 2021). These potential interactions among landscape and climatic factors imply that identification and management of climate-change refugia based on independent effects cannot effectively mitigate biodiversity decline in the future.…”
Section: Introductionmentioning
confidence: 99%
“…1.5 m above a level, grassy surface. As such, these data do not account for forest canopy effects on temperature microclimate (Haesen et al ., 2021). Climate data were extracted using the weathercan package in R (LaZerte & Albers, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…This is a standard Environment Canada weather station that records air temperature in the open, c. 1.5 m above a level, grassy surface. As such, these data do not account for forest canopy effects on temperature microclimate (Haesen et al, 2021). Climate data were extracted using the WEATHERCAN package in R (LaZerte & Albers, 2018).…”
Section: Air Temperature Time Seriesmentioning
confidence: 99%
“…WorldClim is one of the most widely used sources of climate data for ecological studies; however, many alternative methods of generating such datasets have been demonstrated at ecologically meaningful scales. These include downscaling and empirical adjustment of pre‐existing climate surfaces (Abatzoglou et al, 2018; Karger et al, 2017; Kearney et al, 2014, 2020; Kriticos et al, 2012; Poggio et al, 2018), correlative interpolations calibrated using micro‐loggers in forested ecosystems (Ashcroft & Gollan, 2012; Haesen et al, 2021; Lembrechts et al, 2021; Meineri & Hylander, 2017) and techniques that apply geostatistical and spline‐based methods in conjunction with earth observation data (Funk et al, 2015; Hengl et al, 2012; Oyler et al, 2015; Stewart et al, 2017; Stewart & Nitschke, 2017e).…”
Section: Introductionmentioning
confidence: 99%